Perancangan E-Business Berbasis Web Pada Toko Hamzah Batik Menggunakan Metode Analisa SWOT dan PEST - Nadeak, Puja Waldi; M. Anjas Leonardi; M. Irfan Bahri; Putri Taqwa Prasetyaningrum (Universitas Mercu Buana Yogyakarta, 2024)
E-Business is one of the developments in technology and the internet. That is a service used for buying and selling online. E-Business is selling, marketing products through electronic systems such as the internet or other computer networks. In this study the authors found the problems that occurred, namely the absence of a special sales information system for Hamzah Batik to disseminate sales, the unavailability of facilities that function as product marketing media to the public so that it is difficult to provide information about various kinds of products as offered at Hamzah Batik. In this study the method used is SWOT and PEST analysis. SWOT analysis is a strategic planning method for evaluating strengths, weaknesses, opportunities and threats in a business process. As well as this analysis method is used to systematically formulate strategic decisions related to important matters in a company. PEST analysis is a method used to analyze the external environment that can affect the company's business goals. This analysis includes analysis of political, economic, social, and technological factors.